Evaluation Of Antihyperglycemic Effects, Nutritional/Antinutritional Values And Phytochemical Contents Of Ocimum Tenuiflorum Linn - Mousavi, Leila (2018)
The leaves of Ocimum tenuiflorum L. (lamiaceae) (locally known as ruku) has been used to make nasi ulam in Malaysia. Therefore, the present work is aimed to explore the nutritional, antinutritional, and it`s anti diabetic effect on ruku tree. The result of the first phase showed that ruku leaves displayed higher values of the nutritional level (proximate, amino acid profile, fatty acid profile, vitamin and phytochemical content) compared to the stem. In addition, the result of antinutrients level in the ruku leaves and stem displayed within the safe level.